Pengaruh Model Pembelajaran Probing-Prompting Berbantuan Media Sederhana Terhadap Hasil Belajar IPA - Sherina Surya Sahayu; i nyoman jampel; i nyomn laba jayanta (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims at determining the differences in learning outcomes between groups of students who received treatment of probing-prompting models with simple media assisted with groups of students who did not receive treatment of probing-prompting model with simple media assisted on science subjects. This study is quasi-experimental research using non-equivalent design post-test only control group design. The population of this study is the entire class III SDN in Gugus III Banjar District. The sample of this research is SDN 3 Dencarik which amounted to 20 people as experiment group and SDN 2 Dencarik which amounted to 25 people as control group. The methods of data collection are using the test method that was done through multiple choice instrument test of science learning outcomes. The hyphotesis analysis was done by using t-test asissted with SPSS 20. The results showed that there were differences of learning outcomes in the group of students who were given the treatment of probing-prompting model with simple media assisted with the group of students who were not given treatment of probing-prompting model with simple media-assisted learning in the science lessonThus, the probing-prompting learning model with simple media assisted affects the learning outcomes of Science subject on grade III students in Gugus III Banjar District, Buleleng Regency, Year 2017/2018. The suggestion of this research is that it can be used as a guide in further research about simple media assisted probing-prompting learning model especially on IPA.